Analisis Hubungan Balok Kolom Beton Bertulang Proyek Pembangunan Gedung DPRD-Balai Kota DKI Jakarta - Setiawan, Agus (ComTech: Computer, Mathematics and Engineering Applications, 2012)
In terms of structural design of reinforced concrete buildings for earthquake-resistant, the beamcolumn joint is a critical area that needs to be accurately designed properly so that the area is able to dissipate energy in the event of an earthquake. The ability of beam-column joint to deform in the inelastic region provides a structure that has a good ductility, so as to minimize the damage caused by earthquake shaking. This study aims to analyze the design of beam-column connection at the Parliament Building-City Hall of Jakarta. The analysis performed refers to the ”Tata Cara Perhitungan Struktur Beton Untuk Bangunan Gedung”, SNI 03-2847-2002. The analysis results shows that the terms of detailing in the field implementation have not been fulfilled properly.